Blue-emitting fluorophores based on 1,3-benzoxazolyl and 1,3-benzothiazolyl-substituted indoles and carbazoles - Santos, Paula C. S. (2002)
Nine fluorescent compounds based on the indole or carbazole system substituted with 1,3-benzoxazolyl or 1,3-benzothiazolyl groups have been synthesised by condensation of indole or carbazole aldehyde or carboxylic acid precursors with ortho-aminophenol or ortho-aminothiophenol. Four of them are reported for the first time (3, 5, 7 and 8). The compounds were characterised by 1H NMR, IR, UV and elemental analysis or HRMS. Fluorescence spectra were measured, and excitation and emission maxima and fluorescence quantum yields are reported.